From coma to consciousness: Effective extracorporeal clearance in severe phenobarbital overdose - BORA, BHAYOLINA; ISLAM, MOINUL; SONOWAL, AMRIT JYOTI SONOWAL; BORA, ANANTA KUMAR (Indian Journal of Case Reports, 2026)
Phenobarbital remains widely used for epilepsy management in resource-limited settings, but severe overdose can lead to prolonged coma and life-threatening complications. We report a 22-year-old female who presented with deep coma and respiratory failure following intentional ingestion of approximately 100 phenobarbital tablets. Despite optimal supportive care, neurological recovery was delayed with persistently elevated serum drug levels. Two consecutive sessions of intermittent hemodialysis were performed, resulting in rapid clinical improvement and a significant reduction in serum phenobarbital concentration. The patient achieved complete neurological recovery without sequelae. This case highlights the effectiveness of hemodialysis as an accessible extracorporeal modality for enhanced drug elimination in severe phenobarbital poisoning and emphasizes the importance of early identification of candidates for such therapy.